INTEGRATING REWANG PRACTICES INTO CULINARY EDUCATION: A TEACHING INNOVATION USING KENDURI TRADITIONS - Sharif, Mohd Shazali Md; Zulkifali, Wan Ahmad Hasni Wan; Shahril, Aslinda Mohd; Abdullah, Norhidayah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
This study explores the integration of rewang practices, a traditional communal cooking activity, into contemporary culinary education as an innovative teaching approach. Grounded in Malaysia’s rich cultural heritage, the rewang tradition embodies collaboration, knowledge-sharing, and community engagement, offering valuable pedagogical insights for culinary instruction. The research specifically focuses on the preparation of kenduri (feast) traditions. By employing the observation method, this study examines how experiential learning through participation in rewang activities can enhance students’ understanding of culinary processes, teamwork, and cultural identity. Data were collected through structured observations of culinary students participating in a simulated rewang environment that emphasized cooperative food preparation, traditional cooking techniques, and communal event organization. The findings indicate that integrating rewang into the culinary curriculum fosters not only technical skills such as recipe standardization, portion control, and traditional flavour profiling, but also soft skills, including communication, leadership, and cultural appreciation. Moreover, students demonstrated heightened awareness of sustainability and local resource utilization, reflecting values embedded in traditional cooking practices. The study concludes that incorporating rewang practices into culinary education provides a holistic and culturally responsive model of teaching and learning. It bridges academic training with community-based knowledge, reinforcing the social dimensions of food preparation and the importance of cultural continuity. The use of kenduri traditions as teaching contexts underscores the potential of cultural heritage as a dynamic pedagogical tool. This study contributes to the development of culturally grounded culinary professionals equipped with both technical competence and cultural sensitivity, supporting the broader agenda of preserving and revitalizing Malaysia’s intangible culinary heritage within modern educational frameworks.